PP.32 Second-Trimester Miscarriage; Risk Factors from a Large Prospective Cohort. (26th April 2013) - Morris, A; Lutomski, J; Khashan, A; Kenny, L; O'Donoghue, K
Abstract : In the UK and Ireland, second-trimester miscarriage is deﬁned as pregnancy loss after the 14 th and before the 24 th week of gestation 1 . Infection, cervical insufﬁciency, uterine malformations, gene polymorphisms, fetal/placental anomalies and genetic/acquired thrombophilias are known risk factors 1 ; however the literature on this topic is limited. Thus, this study aimed to examine risk factors for second-trimester miscarriage. A nested case-control study was performed using data from the multicentre, prospective Screening for Pregnancy Endpoints (SCOPE) study. Within the SCOPE cohort of 3, 531 healthy, nulliparous women with singleton pregnancies, we identified cases of second-trimester miscarriage. For each case, 5 controls were selected from the SCOPE cohort; controls were matched according to centre of recruitment and age. Descriptive statistics were performed and unadjusted odds ratios were derived to assess risk factors. 8 women experienced a second-trimester miscarriage (2.3 per 1000 pregnancies); mean age was 28.6 years (SD: 6.8). On average, miscarriage occurred at 20 +5 (SD: 20 days). An increased, though insignificant, risk was observed amongst women whose mothers had a preterm birth (OR: 4.11; 95% CI 0.56 – 29.96), maternal alcohol consumption in the first trimester (OR: 2.55, 95% CI 0.47 – 10.76) or vaginal bleeding in the first trimester (OR: 2.4; 95% CI 0.47 – 12.22). Covariates of interest did not confer a significantly increased risk of second-trimester miscarriage, though our analysis was limited by the low incidence of second-trimester miscarriage. The understanding of second-trimester miscarriage and associated risk factors would benefit from prospective case-control studies that involve higher numbers of women. Reference: Edlow AG, Srinivas SK, Elovitz MA. Second-trimester loss and subsequent pregnancy outcomes: What is the real risk? Am J Obstet Gynecol 2007;197: 581.e1–6.